PENGURANGAN EMISI CO2 MELALUI PENGELOLAAN ENERGI LISTRIK DI RUANG PUBLIK HOTEL (Studi Kasus Di Hotel ABC Jakarta) - Riska Melanie; Udi Syahnoedi Hamzah (President University, 2016)
Hotels commonly still use electric energy inefficiently. One kWh consumption equals to 5,2041x10-4 mtCO2 emission. This research discusses about reduction of CO2 emission through electric energy management in hotel’s public spaces. The design was a survey with 90 respondents in 4-star hotel ABC Jakarta. The kWh measurements were conducted in Lobby Hotel ABC. The research was done in 2012 and it showed correlation between workers’ knowledge, attitude and behavior to the quality of electric energy management. The hotel showed low quality of electric energy management. Electric energy use for illumination in Hotel ABC was 3,232.8 kWh/year equals to1.68 mtCO2/year. The experiment was done by using LED lamps with reduction of CO2 results for Lobby Hotel ABC was 55.90% equals to 0.94 mtCO2/year. In conclusion, worker’s behavior gives influence to the quality of electric energy management. To improve the quality of electric energy management, it is recommended to determine electric energy efficiency policy and program, relevant training and working procedures, implementation of best practices and if necessary use LED lamps to replace incandescent and CFL lamps.